Holographic cosmology from “dimensional reduction” of N = 4 SYM vs. AdS5 × S 5 - Bernardo, Heliudson [UNESP]; Nastase, Horatiu [UNESP] (Springer Nature, 2019)
We propose a way to obtain holographic cosmology models for 3+1 dimensional cosmologies vs. 3 dimensional field theories from a “dimensional reduction” procedure, obtained by integrating over the time direction, of (modifed) standard holographic duals of 3+1 dimensional field theories. The example of a modified N = 4 SYM vs. AdS5 × S5 is presented, and in perturbation theory doesn’t match observations, though at strong coupling it might. But the proposed mechanism is more general, and it could in principle be applied to other top down holographic models.
Keywords: AdS-CFT Correspondence; Cosmology of Theories beyond the SM